2017
DOI: 10.1051/shsconf/20173411002
|View full text |Cite
|
Sign up to set email alerts
|

Post Implementation of Goods and Services Tax (GST) in Malaysia: Tax Agents’ Perceptions on Clients’ Compliance Behaviour and Tax Agents’ Roles in Promoting Compliance

Abstract: Abstract. The Malaysian government introduced the Goods and ServicesTax (GST) starting from 1 April 2015 to enhance the revenue collections and mitigate the transfer pricing manipulation. Tax agents play a significant role to help businesses to comply with GST law and regulations. After one year of GST implementation, it is vital to understand tax agents' perceptions on clients' compliance behaviour and tax agents' roles in influencing compliance. A total of 30 registered tax agents completed a survey question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Senthuran Elalingam, the indirect tax leader at Deloitte Malaysia mentioned that many businesses find that the administration cost associated with complying with the GST to be high as well as the cash-flow costs due to delayed payments of refunds (Smith, 2018). Muhammad (2017) found that majority of the tax agents in Malaysia strongly agree that many of their clients feel burdened with GST requirements. She also found that the tax agents" clients rely on their tax agent assistance to comply with the GST obligations.…”
Section: Tax Practitionersmentioning
confidence: 99%
“…Senthuran Elalingam, the indirect tax leader at Deloitte Malaysia mentioned that many businesses find that the administration cost associated with complying with the GST to be high as well as the cash-flow costs due to delayed payments of refunds (Smith, 2018). Muhammad (2017) found that majority of the tax agents in Malaysia strongly agree that many of their clients feel burdened with GST requirements. She also found that the tax agents" clients rely on their tax agent assistance to comply with the GST obligations.…”
Section: Tax Practitionersmentioning
confidence: 99%
“…For example, in ensuring the taxpayers’ return and filing are correct, tax authorities incur additional costs and resources for checking purposes. Similarly, tax agents are hired to ensure the tax return submitted are correct (Muhammad, 2017; Isa et al , 2014) as taxpayers may face penalty if non-compliance is detected (Saad et al , 2014). Thirdly, tax complexities may also cause unfairness as not all taxpayers are equally able to take advantage of the various complexities of the tax system (James et al , 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study on tax agents in Malaysia shows that their clients felt burdened by the requirements needed by the GST act as there is a difficulty to understand how to comply with the GST requirements and to avoid any penalties from non-compliance (Muhammad, 2017). Due to the difficulties, many of the taxpayers delegated their GST matters to their tax agents and the agents needed to ensure the filing was done correctly by asking for additional information from their clients as the clients were not sure which information was needed for the filing (Muhammad, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations